Tumor targeted gold nanoparticles for FRET-based tumor imaging and light responsive on-demand drug release. Issue 41 (23rd September 2015) - Han, Kai; Zhu, Jing-Yi; Wang, Shi-Bo; Li, Zi-Hao; Cheng, Si-Xue; Zhang, Xian-Zheng
Abstract : Multifunctional AuNPs for MMP-2 responsive tumor imaging and on-demand drug release were designed. A good chemotherapy and photodynamic therapy combination with minimized side effects was realized. Abstract : In this work, a new type of gold nanoparticles (AuNPs) is designed to achieve the programmed tumor imaging and light manipulated controlled drug release. In vitro results demonstrate that these AuNPs undergo matrix metalloproteinase-2 (MMP-2) responsive fluorescence recovery of photosensitizers, protoporphyrin IX (PpIX), in the tumor region, which can differentiate tumor cells from healthy ones. Subsequently, light irradiation activates PpIX, which cleaves the reactive oxygen species (ROS) sensitive thioketal linker, leading to on-demand drug release as well as free drug diffusion into nuclei. More importantly, in vitro studies indicate the good performance of AuNPs in combined photodynamic therapy and chemotherapy with limited side effects. This AuNP based nanoplatform provides great potential for tumor targeted on-demand combination therapy.